2016
DOI: 10.1037/dev0000093
|View full text |Cite
|
Sign up to set email alerts
|

Language-general biases and language-specific experience contribute to phonological detail in toddlers’ word representations.

Abstract: Although toddlers in their 2nd year of life generally have phonologically detailed representations of words, a consistent lack of sensitivity to certain kinds of phonological changes has been reported. The origin of these insensitivities is poorly understood, and uncovering their cause is crucial for obtaining a complete picture of early phonological development. The present study explored the origins of the insensitivity to the change from coronal to labial consonants. In cross-linguistic research, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Two approaches were deployed to analyze the data for this study: t-tests, which are traditionally used to analyze infant lookingtime data, and mixed effects models, which have been making their way into the analysis of infant behavioral data (Consortium, 2017;Tsuji, Fikkert, Yamane, & Mazuka, 2016). The mixed-effect model may have been more sensitive to the effect of rhyme on infants' looking behavior, as it simultaneously accounts for variance introduced by individual participants as well as individual songs.…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches were deployed to analyze the data for this study: t-tests, which are traditionally used to analyze infant lookingtime data, and mixed effects models, which have been making their way into the analysis of infant behavioral data (Consortium, 2017;Tsuji, Fikkert, Yamane, & Mazuka, 2016). The mixed-effect model may have been more sensitive to the effect of rhyme on infants' looking behavior, as it simultaneously accounts for variance introduced by individual participants as well as individual songs.…”
Section: Discussionmentioning
confidence: 99%
“…Test trials were excluded if (1) a child looked less than 500 ms during the 2000 ms post-naming window (e.g., Quam and Swingley, 2010 ; Singh et al, 2014 ; Tsuji et al, 2016 ), (2) the participant fixated only one of two objects during the 2500 ms pre-naming window (e.g., White and Morgan, 2008 ; Mani and Plunkett, 2011 ; Singh et al, 2015 ; Buckler and Fikkert, 2016 ), (3) an equipment or experimenter error occurred, and (4) if a participant refused to participate (e.g., by getting up and walking around) and the experiment had to be aborted.…”
Section: Methodsmentioning
confidence: 99%
“…A block was excluded if (1) a participant did not contribute at least one valid trial per condition (CP and MP) during the test phase (e.g., Buckler and Fikkert, 2016 ; Tsuji et al, 2016 ), and (2) total looking time during target and/or distracter learning trials was under 20 s out of a total of 60 s (e.g., Tsuji et al, 2016 ). The latter criterion is based on the assumption that children who pay more attention to the novel objects during learning should be better able to retain the novel word-object mapping ( Hilton and Westermann, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Altvater-Mackensen et al (2014) reported a similar asymmetry for 18-month-olds in a preferential looking study with fricative onsets (e.g., vis “fish” mispronounced as zis ). Tsuji et al (2016) presented results on asymmetries in newly learned words with Japanese and Dutch toddlers. In their experiment, 18-month-olds learned two novel, coronal-onset words for two novel objects in a mixed live learning and screen-based learning procedure.…”
Section: The Broad View Of Underspecification In Developing Lexical R...mentioning
confidence: 99%